Bioprocess Optimization for the Production of Aromatic Compounds With Metabolically Engineered Hosts: Recent Developments and Future Challenges - Braga, Adelaide; Faria, Nuno (Frontiers in Bioengineering and Biotechnology, 2020)
The most common route to produce aromatic chemicals - organic compounds containing at least one benzene ring in their structure - is chemical synthesis. These processes, usually starting from an extracted fossil oil molecule such as benzene, toluene, or xylene, are highly environmentally unfriendly due to the use of non-renewable raw-materials, a high energy consumption and the usual production of toxic by-products. An alternative way to produce aromatic compounds is extraction from plants. These extractions typically have a low yield and a high purification cost. This motivates the search for alternative platforms to produce aromatic compounds through low-cost and environmentally friendly processes. Microorganisms are able to synthesize aromatic amino acids through the shikimate pathway. The construction of microbial cell factories able to produce the desired molecule from renewable feedstock becomes a promising alternative. This review article focuses on the recent advances in microbial production of aromatic products, with a special emphasis on metabolic engineering strategies, as well as bioprocess optimization. The recent combination of these two techniques has resulted in the development of several alternative processes to produce phenylpropanoids, aromatic alcohols, phenolic aldehydes, and others. Chemical species that were unavailable for human consumption due to the high cost and/or high environmental impact of their production, have now become accessible.